Reviews of Texts for Classroom Use (Teaching theology and religion, 2005)
Books reviewed: Dianne Oliver, Book and Resource Review Editor University of Evansville Daoism: A Short Introduction. By James Miller. Oxford: Oneworld Publications, 2003. xviii + 174 pages. ISBN 1-85168-315-1. USD17.95. Reviewed by John M. Thompson Christopher Newport University The Protestant Reformation: Beliefs and Practices. By Madeleine Gray. Portland, Ore.: Sussex Academic Press, 2003. 262 pages. ISBN: 1-903900-11-5. USD22.50. Reviewed by Jason E. Vickers Hood Theological Seminary True Religion. By Graham Ward. Malden, Mass.: Blackwell Publishing, 2003. 168 pages. ISBN 0-63122174-3. USD20.95. Reviewed by Debra Mubashshir Majeed Beloit College Mediating Religion: Conversations in Media, Religion, and Culture. Edited by Jolyon Mitchell and Sophia Marriage. London and New York: T & T Clark, 2003. xv + 407 pages. ISBN 0-567-08867-7. Cloth USD115.00. ISBN 0-567-08807-3. Paper USD34.95. Reviewed by Richard S. Ascough Queen's Theological College